2017
DOI: 10.3389/fphar.2017.00380
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Properties and Molecular Mechanisms of Thymol: Prospects for Its Therapeutic Potential and Pharmaceutical Development

Abstract: Thymol, chemically known as 2-isopropyl-5-methylphenol is a colorless crystalline monoterpene phenol. It is one of the most important dietary constituents in thyme species. For centuries, it has been used in traditional medicine and has been shown to possess various pharmacological properties including antioxidant, free radical scavenging, anti-inflammatory, analgesic, antispasmodic, antibacterial, antifungal, antiseptic and antitumor activities. The present article presents a detailed review of the scientific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
226
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(234 citation statements)
references
References 255 publications
(342 reference statements)
4
226
0
4
Order By: Relevance
“…These chemicals can interact with neuromodulator octopamine, a neurotransmitter unique to insects, and also induce neurotoxicity via effects on gated chloride channels GABA. 12,33 Concerning the stability, thymol has antioxidant property and can be susceptible to degradation by temperature, light and oxygen to generate phenoxide radicals that further proceed to oxidative and polymerization reactions, 34,35 which may result in a loss of insecticidal efficacy. This phenomenon is consistent with the results obtained by Pavela that post-application temperature affected to the insecticidal activity of thymol and Thymus vulgaris oil against Spodoptera littoralis and Culex quinquefasciatus larvae.…”
Section: Discussionmentioning
confidence: 99%
“…These chemicals can interact with neuromodulator octopamine, a neurotransmitter unique to insects, and also induce neurotoxicity via effects on gated chloride channels GABA. 12,33 Concerning the stability, thymol has antioxidant property and can be susceptible to degradation by temperature, light and oxygen to generate phenoxide radicals that further proceed to oxidative and polymerization reactions, 34,35 which may result in a loss of insecticidal efficacy. This phenomenon is consistent with the results obtained by Pavela that post-application temperature affected to the insecticidal activity of thymol and Thymus vulgaris oil against Spodoptera littoralis and Culex quinquefasciatus larvae.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant properties may be related to its phenolic structure, which may adsorb and neutralize free radicals and exhibit redox properties (Yu et al, 2016). This compound scavenges hydroxyl free radicals and produces phenoxyl radicals, major transient species (Nagoor Meeran et al, 2017), being more active than the synthetic antioxidant terc-butylated hydroxytoluene in vitro (Gavaric, Smole Mozina, Kladar, & Bozin, 2015). As an example, Gavaric et al (2015) reported the following values for the IC 50 of thyme essential oil (41.6% of thymol) and thymol: 0.2 and 28.82 μg/ml, respectively.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…It was obtained in its pure form some 134 years later by Lallemand (1853). Nevertheless, thymol extract from the thyme plant was used thousands of years ago by the ancient Egyptians as a preparation to help preserving mummies (Nagoor Meeran, Javed, Al Taee, Azimullah, & Ojha, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is especially noteworthy as thymol is one of the most potent phytochemicals present in black seed. Various studies have described its antioxidant, antitumor, antimicrobial, and anti-inflammatory activities (Meeran, Javed, Al Taee, Azimullah, & Ojha, 2017). Its ability to act as an anti-cancer agent is proposed to be via pathways, such as antiproliferation, cell cycle arrest, and apoptosis (Li et al, 2017).…”
Section: H Nmr Analysis Of Oilsmentioning
confidence: 99%